The relationships between coping, occupational stress, and emotional intelligence in newly hired oncology nurses. Issue 2 (4th December 2018) - Mazzella Ebstein, Ann M.; Sanzero Eller, Lucille; Tan, Kay See; Cherniss, Cary; Ruggiero, Jeanne S.; Cimiotti, Jeannie P.
Abstract: Objectives: Associations between the varying levels of emotional intelligence in newly hired oncology nurses and their responses to stress and coping were examined. The secondary aim was to analyze whether emotional intelligence could moderate their choice of problem‐focused or emotion‐focused coping strategies. Methods: Newly hired nurses ( n = 114) were recruited from a national cancer institute. Data were collected through surveys using the Ways of Coping Questionnaire, the Nursing Stress Scale, and the Emotional Quotient Inventory between the eighth and twelfth weeks post‐hire date. Descriptive and bivariate statistical analyses were conducted on all variables. Regression models determined whether emotional intelligence moderated the choice of coping strategies. Results: Emotional intelligence had a mean value of M = 105.24, SD = 13.02, and occupational stress scores were M = 65.57, SD = 15.68. Significant negative correlations were found for occupational stress and problem‐focused coping ( r = −.189, P = .022), emotional intelligence and emotion‐focused coping ( r = −.340, P = .000), and emotional intelligence and occupational stress ( r = −.428, P < 0.001). Positive correlations were noted between occupational stress and emotion‐focused coping ( r = .189, P = .022) and emotional intelligence and problem‐focused coping ( r = .340, P = .000). Emotional intelligence did not predict the choice of coping strategies. Conclusions: Although emotional intelligence did not moderate coping strategies in newly hired nurses, using problem focused coping to address occupational stress during the initial employment period may be a protective factor for coping with stress in the oncology workplace.